Inserção e integração da sustentabilidade na cultura do Instituto Federal de Goiás - Câmpus Itumbiara - Barroso, Aline Silva (2015)
Sustainability has become an important issue both in academic and in organizational debates. The concept of sustainable development appeared in the middle 1980 s, and it was after the United Nations Conference, that took place in Rio de Janeiro in 1992, that the theme started being spread and turned popular. In the perspective of the Triple Bottom Line of Elkington (2012), sustainability assures the equilibrium among social, environmental and economic dimensions. The present study, having qualitative nature and a descriptive character, had as a goal to analyze sustainability as value at the Federal Institute of Education, Science and Technology of Goiás (IFG) Itumbiara Campus, considering the perspectives proposed by Meyerson and Martin (1987). The method used was the one about case studies and the data collecting happened in three ways: 1) analysis of organizational documents and publishing done inside the institution and in social networks; 2) interviews with servers; and 3) nonparticipant observation. The data were analyzed by using documental analysis techniques and classical content analysis, with a triangulation done afterwards about them. The results indicate that at the IFG- Itumbiara Campus, sustainability is not in the level of integration among the institution servants. Another finding of the paper was that there is no clarity concerning the meaning of the term in its fullness.